Digital Entrepreneurship Literacy Through Online Selling Training at SMK Xaverius Palembang - Fransiska Soejono; Ming Chen; Agatha Septianna S.R; Andrew Gunawan; Yukie Jocelyn (Jurnal Abdimas Mandiri, 2026)
Digital transformation has reshaped how products are promoted, sold, and trusted, creating new opportunities for vocational students to become young entrepreneurs. However, the partner school reported limited student understanding of entrepreneurship practices supported by e-commerce and digital platforms. This community service program aimed to strengthen digital entrepreneurship literacy through structured online selling training at SMK Xaverius Palembang. The activity was conducted on 3 September 2025 using lectures, video-based learning, and simulations. Program evaluation used a 10-item multiple-choice questionnaire covering core competencies such as online selling concepts, marketplace knowledge, digital marketing, product photography, customer service, target market, branding, and performance indicators. Descriptive analysis was applied to summarize correct and incorrect responses. The results from 131 respondents showed an overall correct-response rate of 96.4%. Perfect scores (100%) were achieved on items related to the definition of online selling, identifying popular marketplaces, and the importance of product photos. The lowest percentages of correct responses were recorded for items concerning the advantages of online selling and the concept of target markets, both at 85.5%. These findings describe participants’ understanding of online selling topics at the end of the activity. Follow-up sessions should emphasize segmentation, positioning, and customer value communication to support sustainable digital entrepreneurship